Existence of Criminal Trials against Electoral Crimes of Regional Heads (Analysis of Pekanbaru High Court Decision Number 40/Pid.Sus/2021/PT.PBR) - Mhd. Teguh Syuhada Lubis (Budapest International Research and Critics University, 2021)
The process of organizing regional head elections is certainly not without constraints and dynamics. There are many violations found in every stage of both administrative violations, violations of the code of conduct and criminal violations. After several changes and changes in the rules on the election of regional heads (Governors, Regents/Mayors), in the end even though Law No. 6 of 2020 describes the special crimes of elections in it, but in its application can not override the provisions of the Criminal Code. One of them is related to the criminal act of probation contained in Article 53 and Article 54 of the Criminal Code. The research conducted is normative juridical research using secondary data by processing data from primary legal materials, secondary legal materials and tertiary legal materials. Based on the results of the study, it is known that the handling of electoral crimes of regional heads in Indonesia, namely through integrated law enforcement (Gakkumdu) centers consisting of Election Supervisory Board (Bawaslu), Police and Prosecutors. Furthermore, criminal liability for perpetrators of Criminal Trials in the General Election of the Regional Head must first meet the criminal elements in Article 187A paragraph (1) Law No. 6 Year 2020 concerning the Election of Governors, Regents and Mayors and Article 53 paragraph (1) of the Criminal Code. Once both elements of the article are fulfilled, against the severity of the prison sentence and the fine should be reduced by one-third of the maximum penalty in Article 187A paragraph (1) that is to a maximum of 4 years in prison. The last legal analysis of the Pekanbaru High Court's Decision No. 40/Pid.Sus/2021/PT.PBR the judge's decision has been appropriate the judge gave a sanction of 3 (three) years in prison to the perpetrator. It is in accordance with the provisions of Article 187A of Law Number 6 of 2020 Jo Article 53 paragraph (1) of the Criminal Code. Because the intention of the act and the nature of harming the interests of others are fulfilled.